2012
DOI: 10.3126/ijim.v1i1.6639
|View full text |Cite
|
Sign up to set email alerts
|

Recent trend of bacterial aetiology of lower respiratory tract infection in a tertiary care centre of Nepal

Abstract: INTRODUCTION:Lower respiratory tract infections (LRTIs) are among the most common infectious diseases of humans. This study focused on determining the recent trend of bacterial aetiology of LRTIs among the patients attending Tribhuvan University Teaching Hospital (TUTH) in Kathmandu. MATERIALS AND METHODS:This was a prospective study conducted over a period of six months in the bacteriology laboratory of TUTH. A total of 1120 specimens representing lower respiratory tract were received from patients with suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 19 publications
9
33
2
Order By: Relevance
“…Similar organisms were also observed in present study [14]. In HIV negative hospital attending patients, the prevalence of bacterial LRTIs had been reported to be 44.4 %-50.4 % [9,13]. The lower yield of pathogens in this study as compared to other studies might be attributable to various factors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar organisms were also observed in present study [14]. In HIV negative hospital attending patients, the prevalence of bacterial LRTIs had been reported to be 44.4 %-50.4 % [9,13]. The lower yield of pathogens in this study as compared to other studies might be attributable to various factors.…”
Section: Discussionsupporting
confidence: 87%
“…In Nepal, concerns on LRTIs are increasing among the HIV infected cases because they are being revealed as the important opportunistic infections among these cohorts. LRTIs are common not only among the HIV sero-positive cases but also the commonest domiciliary and nosocomial infections among the general population [9]. The risk of development of invasive pneumococcal diseases is higher among the HIV positive cases than the HIV sero-negative population [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study among the 109 sputum samples processed bacterial etiology was isolated in 71 (61.54%) samples. This is similar to the findings of Mishra et al (4) and Ramana et al (5) in which the isolation rates were 44% and 39.4% respectively. Similar higher prevalence rates of about 57.4% was shown in a study done by Thomas et al (7) tract infections than female sex.…”
Section: Resultssupporting
confidence: 82%
“…There was a predominance of Gram negative bacterial cause (70.9%) among the LRTI's as observed by a recent study from Nepal by SK Mishra et al who reported 84.1% occurrence. The same study reported Haemophilus influenzae (21%) as the most common Gram negative bacterium isolated and Streptococcus pneumoniae as a predominant Gram positive bacterial (8.6%) cause in contrast to the present study [18]. A recent study by Yuhua Zhou et al from China which included both molecular methods and automated culture methods to study the LRT microbiota from sputum samples, revealed that Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus spp were predominant bacterial species associated with LRTI's al [19].…”
Section: Discussioncontrasting
confidence: 54%